Effects of Immigration Enforcement Legislation on Hispanic Pediatric Patient Visits to the Pediatric Emergency Department. (December 2013) - Beniflah, Jacob D.; Little, Wendalyn K.; Simon, Harold K.; Sturm, Jesse
Objective . To compare the visits by Hispanic patients to the pediatric emergency department (PED) before and after passage of Georgia House Bill 87 (HB87). This bill grants local law enforcement the authority to enforce immigration laws. Methods . A retrospective chart review of all Hispanic patients who presented to the PED in a 4-month period after implementation of HB87 in 2011 was conducted and compared with the same period in 2009 and 2010. Data compared included patient acuity score, disposition, payer status, and demographics. Results . Fewer Hispanic patients presented to the ED after passage of the bill (18.3% vs 17.1%, P < .01), more patients were high acuity, and more patients were admitted to the hospital. Conclusion . The Hispanic population was the only group to see a decrease in visits and increase in acuity in the post-bill period. These results suggest potential adverse health effects on members of a specific group as a result of immigration legislation.